Synthesis, crystal structure and magnetic properties of H2tppz[ReCl6] and [Cu(bpzm)2(μ-Cl)ReCl3(μ-ox)Cu(bpzm)2(μ-ox)ReCl3(μ-Cl)]n. Issue 39 (15th September 2015) - Gryca, I.; Palion-Gazda, J.; Machura, B.; Penkala, M.; Kruszyński, R.; Cano, J.; Lloret, F.; Julve, M.
Abstract : The magneto-structural study of a mononuclear H2 tppz[ReCl6 ] ionic salt and a heterobimetallic [Cu(bpzm)2 (μ-Cl)ReCl3 (μ-ox)Cu(bpzm)2 (μ-ox)ReCl3 (μ-Cl)] n chain with alternating single chloro and didentate/monodentate oxalato bridges is presented here. Abstract : Two new Re(iv ) compounds of formulae H2 tppz[ReCl6 ] (1 ) and [Cu(bpzm)2 (μ-Cl)ReCl3 (μ-ox)Cu(bpzm)2 (μ-ox)ReCl3 (μ-Cl)] n (2 ) [tppz = 2, 3, 5, 6-tetrakis(2-pyridyl)pyrazine and bpzm = bis(pyrazolyl-1-yl)methane] have been prepared and their crystal structures determined by X-ray diffraction on single crystals. Compound1 is a mononuclear species whose structure consists of octahedral hexachlororhenate(iv ) anions and diprotonated H2 tppz 2+ cations which are arranged in the unit cell as alternating anionic and cationic layers, held together by electrostatic forces. The structure of2 is made up of alternating [Cu(1)(bpzm)2 ] 2+ and [(ox)ReCl3 (μ-Cl)Cu(2)(bpzm)2 (μ-Cl)ReCl3 (ox)] 2− entities interlinked by oxalate bridges to afford a neutral heterobimetallic chain. The oxalate group adopts the didentate (at Re)/monodentate (at Cu) bridging mode. The magnetic behavior of1 and2 has been investigated over the temperature range 1.9–295 K.1 is a magnetically diluted Re(iv ) complex, the relatively large value of the zero-field splitting of the ground level [ D = −15.8(2) cm −1 ] accounting for the variation of χ M T in the low temperature range. Weak intrachain ferromagnetic interactions between Re(iv ) and Cu(ii ) through oxalate ( J 1 = +0.15 cm −1 ) and single chloro ( J 2 = +4.9 cm −1 ) bridges occur in2 which are obscured by the large zero-field splitting of the Re(iv ) ion ( D Re = 42 cm −1 ). In addition, interchain antiferromagnetic interactions are also involved in2 which are responsible for the metamagnetic behavior observed, the value of the critical dc magnetic field ( H c ) being 20 kOe.